Sowing seeds of resilience: Transforming Kenya's Makueni County with climate-smart agriculture - Kinyua, Ivy Wambui; Waswa, Boaz Shaban; Templer, Noel; Mucemi, Ann; Nzuki, Esther (2023)
A farmer training on climate information services/Climate-smart agriculture technologies in Makueni County